Ecuador's inflation - Vayas, Tatiana (2014)
Ecuador's inflation period 1999-2014 is analyzed. DOI: https://doi.org/10.31164/bcoyu.1.2014.531 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/531